3-D shape analysis of palatal surface in patients with unilateral complete cleft lip and palate - Rusková, Hana; Bejdová, Sárka; Peterka, Miroslav; Krajíček, Václav; Velemínská, Jana (Journal of cranio-maxillofacial surgery, 2014)
Facial development of patients with unilateral complete cleft lip and palate (UCLP) is associated with many problems including deformity of the palate. The aim of this study was to evaluate palatal morphology and variability in patients with UCLP compared with Czech norms using methods of geometric morphometrics. The study was based on virtual dental cast analysis of 29 UCLP patients and 29 control individuals at the age of 15 years. The variability of palatal shape in UCLP patients was greater than that in nonclefted palates. Only 24% of clefted palates fell within the variability of controls. The palatal form of UCLP patients (range from 11.8 to 17.2 years) was not correlated with age. Compared with control palates, palates of UCLP patients were narrower, more anteriorly than posteriorly. Apart from the praemaxilla region, they were also shallower, and the difference increased posteriorly. The UCLP palate was characterised by the asymmetry of its vault. The maximum height of the palatal vault was anterior on the clefted side, whereas it was posterior on the nonclefted side. The slope of the UCLP palate was more inclined compared with the control group. The praemaxilla was therefore situated more inferiorly.
Keywords: věkové faktory; mladiství; patro; uživatelské rozhraní počítače; maxila; dítě; rozštěp rtu; Maxilla; rozštěp patra; Cephalometry; Cleft Palate; anatomická značka; Humans; Cleft Lip; kefalometrie; Plastic Surgery Procedures; Anatomic Variation; Imaging, Three-Dimensional; Male; User-Computer Interface; Image Processing, Computer-Assisted; Child; zobrazování trojrozměrné; zákroky plastické chirurgie; zubní modely; Anatomic Landmarks; anatomická variace; Palate; Adolescent; Models, Dental; počítačové zpracování obrazu; lidé; Age Factors; mužské pohlaví